Characterization of soybean chitinase genes induced by rhizobacteria involved in the defense against Fusarium oxysporum - Chen, Jheng-Yan; Sang, Hyunkyu; Chilvers, Martin I.; Wu, Chih-Hang; Chang, Hao-Xun (Frontiers in Plant Science, 2024)
Rhizobacteria are capable of inducing defense responses via the expression of pathogenesis-related proteins (PR-proteins) such as chitinases, and many studies have validated the functions of plant chitinases in defense responses. Soybean (Glycine max) is an economically important crop worldwide, but the functional validation of soybean chitinase in the defense responses remains limited. In this study, genome-wide characterization of soybean chitinases was conducted, and defense contribution of three chitinases (GmChi01, GmChi02, or GmChi16) were validated in Arabidopsis transgenic lines against the soil-borne pathogen Fusarium oxysporum. Compared to the Arabidopsis Col-0 and empty vector controls, the transgenic lines with GmChi02 or GmChi16 exhibited less chlorosis symptoms and wilting. While GmChi02 and GmChi16 enhanced defense to F. oxysporum, GmChi02 was the only one significantly induced by Burkholderia ambifaria. The observation indicated that plant chitinases may be induced by different rhizobacteria for defense responses. The survey of 37 soybean chitinase gene expressions in response to six rhizobacteria observed a diverse inducibility, where only 10 genes were significantly up-regulated by at least one rhizobacterium and 9 genes did not respond to any of the rhizobacteria. Motif analysis on soybean promoters further identified not only consensus but also rhizobacterium-specific transcription factor-binding sites for the inducible chitinase genes. Collectively, these results confirmed the involvement of GmChi02 and GmChi16 in defense enhancement, and highlighted a diverse inducibility of 37 soybean chitinases encountering F. oxysporum and six rhizobacteria.